2019
DOI: 10.1103/physrevb.100.060404
|View full text |Cite
|
Sign up to set email alerts
|

Polarized inelastic neutron scattering of nonreciprocal spin waves in MnSi

Abstract: We report spin-polarized inelastic neutron scattering of the dynamical structure factor of the conical magnetic helix in the cubic chiral magnet MnSi. We find that the spectral weight of spinflip scattering processes is concentrated on single branches for wavevector transfer parallel to the helix axis as inferred from well-defined peaks in the neutron spectra. In contrast, for wavevector transfers perpendicular to the helix the spectral weight is distributed among different branches of the magnon band structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…It can differentiate magnon creation and annihilation processes [15], which relates to the magnon polarization because the total spin of magnon plus neutron must be conserved in the scattering process. The symmetry of magnetic fluctuations [16] and non-reciprocal magnons [17] can also be directly investigated. More recently the "chiral terms" [18] were used to measure chiral magnetic order [19] and excitations in paramagnetic [20] and chiral phases [21].…”
Section: Takedownmentioning
confidence: 99%
“…It can differentiate magnon creation and annihilation processes [15], which relates to the magnon polarization because the total spin of magnon plus neutron must be conserved in the scattering process. The symmetry of magnetic fluctuations [16] and non-reciprocal magnons [17] can also be directly investigated. More recently the "chiral terms" [18] were used to measure chiral magnetic order [19] and excitations in paramagnetic [20] and chiral phases [21].…”
Section: Takedownmentioning
confidence: 99%
“…Magnon band structures are nontrivial in chiral magnets because of bulk Dzyaloshinskii-Moriya interaction (DMI) [1][2][3][4][5][6]. As a consequence of the asymmetric exchange interaction, bulk DMI introduces non-reciprocity for the spin waves [5,[7][8][9][10][11][12][13]. Therefore chiral magnets can serve as non-reciprocal microwave devices [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spectra for momentum transfers parallel to the skyrmion tubes were recorded (Fig. 4), which display the characteristics of conventional nonreciprocal magnons akin those observed in the topologically trivial phases ( 21 25 , 33 , 34 ). The scattering geometries were chosen carefully to further distinguish nuclear and magnetic scattering ( 17 ).…”
mentioning
confidence: 99%
“…Here, we used polarized inelastic neutron scattering to determine the predicted dispersion and orbital motion of magnons in the skyrmion lattice of MnSi. Neutron and microwave studies of spin excitations in MnSi have been reported for the topologically trivial magnetic phases, namely the helical, conical, and spin-polarized states ( 21 25 ) as well as the paramagnetic regime ( 26 31 ). This work has revealed, across the entire Brillouin zone, well-defined dispersive, nonreciprocal spin waves and spin fluctuations in the ordered states and the paramagnetic regime, respectively.…”
mentioning
confidence: 99%